NON-PHARMACOLOGICAL THERAPY TO REDUCE CHILDREN'S FEAR OF INVASIVE PROCEDURES: SCOPING REVIEW - Rahmawati, Sri; Rakhmawati, Windy; Hendrawati, Sri (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2025)
Invasive procedures, such as intravenous catheterization, intramuscular injection, and blood sampling, often induce fear and pain in children, thus negatively impacting their experience and triggering needle phobia. Therefore, non-pharmacological interventions, such as distraction techniques, are considered effective in reducing fear and pain during such procedures. This review aims to identify and analyze various effective non-pharmacological distraction techniques for reducing children's fear during invasive procedures in hospitals. This scoping review was conducted according to the PRISMA-ScR framework. Literature searches were conducted in the PubMed, ScienceDirect, Scopus, EBSCO-host, and Google Scholar databases using the relevant keywords. Articles meeting the inclusion criteria (RCTs and quasi-experimental studies, published between 2020 and 2025, in English) were assessed for quality using the JBI tool. Data were extracted and analyzed thematically. Of the 1,620 articles, 15 studies met the inclusion criteria. Distraction techniques were categorized into two groups: (1) passive distraction (e.g., Buzzy, listening to music, watching cartoons, and virtual reality) and (2) active distraction (e.g., TICK-B, blowing balloons, interacting with animals, and drama games). Both techniques were effective in reducing children's fear, pain, and anxiety, with Buzzy and TICK-B being the most commonly used interventions. Both active and passive distraction techniques are equally effective in reducing children's fear of invasive procedures. These findings provide guidance for healthcare professionals in selecting interventions appropriate to a child's needs and clinical context. Further research is needed to explore the effectiveness of these techniques in different age groups and geographical regions.